Les incidences sectorielles et régionales du libre-échange Canada-Etats-Unis - Denis, Jean-Émile; Stavrinidis, Christine; Tessier, Serge (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1986)
The debate on the advantages and disadvantages of free trade between Canada and the U.S. has intensified over the past months. Reluctance towards such an option in trading policy has increased and views differ more and more on the subject, particularly concerning its sector-based and regional consequences. Following a survey of the findings of earlier economic studies, the consequences of free trade between Canada and the U.S. are assessed as regards job distribution in the manufacturing industry. Estimates are derived from studies made by Harris and Cox which allow comparison to be made between the consequences of bilateral and multilateral free trade s. Contrary to the views expressed by the Royal Inquiry Commission, the results lead to the conclusion that bilateral free trade will bring about a marked relocation of the labour force. It turns out that job opportunity in areas with high level of employment would grow, as would the specialization of Quebec in these areas, as compared to Ontario.